2019
DOI: 10.22437/jmj.v7i1.7059
|View full text |Cite
|
Sign up to set email alerts
|

THE HIGH DOSE TOXICITY OF BETEL NUT (Areca catechu L.) ON REPRODUCTION ORGAN OF RATS

Abstract: ABSTRACT Background : The use of long-term herbal medicines and high doses can damage organs, including the reproductive organs. Betel nut (Areca catechu L.) is one of the herbal ingredients that is consumed as a stamina enhancing beverage. The purpose of this study was to determine the effect of longterm treatment of raw betel nut at a dose of 10,000 mg/kg on testicular and ovary tissue of rats. Rats were Rattus norvegicus, Sprague Dawley strain, 2-3 months.  Methods : Tweenty rats divided into 2 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Several studies have shown that areca nuts can cause infertility in animal trials. Administration of high doses of areca nuts can cause motility and morphology disorders of rat spermatozoa or testicular tissue abnormalities (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that areca nuts can cause infertility in animal trials. Administration of high doses of areca nuts can cause motility and morphology disorders of rat spermatozoa or testicular tissue abnormalities (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Kidneys and the liver are organs often used as parameters for assessing toxicity. Several studies show that extract of areca nuts or arecoline also cause damages to other organs, such as the liver and kidneys, especially in long-term administration and high doses (9,(16)(17)(18)(19)(20). Determination of an effective and safe dose range is needed to develop areca nuts as a candidate for an oral herbal male contraceptive.…”
Section: Introductionmentioning
confidence: 99%